Everolimus for the treatment of epithelioid hemangioma: a case report (Medical Journal of Indonesia, 2021)
Epithelioid hemangioma is a rare benign vascular tumor manifested as slow-growing subcutaneous or dermal nodules. A previously therapeutic strategy involved surgical excision and sclerotherapy. However, no standard treatment has been established. Here, we reported an atypical case of epithelioid hemangioma that had a locally aggressive behavior and was successfully treated with everolimus, a rapamycin analog used for cancer therapy. A 1-year-old boy presented with an ulcerated lump in the left palmar region. The imaging test results, confirmed through histopathologic examination, suggested a diagnosis of epithelioid hemangioma. Targeted therapy with everolimus was administered orally because of a minimal response to initial transarterial sclerotherapy. The patient achieved a satisfactory response with a significantly reduced lesion size and improved hand function after a 2-year follow-up. This finding showed that patients with locally aggressive forms of epithelioid hemangioma may significantly benefit from everolimus as a potential targeted therapy.